Asthma control and health-related quality of life one year after inpatient pulmonary rehabilitation: the ProKAR Study. (August 2015) - Lingner, Heidrun; Ernst, Stefanie; Groβhennig, Anika; Djahangiri, Nino; Scheub, David; Wittmann, Michael; Schultz, Konrad
Abstract Objectives: Although pulmonary rehabilitation (PR) is commonly used for asthmatics in many countries, so far there are no studies addressing the question of whether and for how long an improvement in asthma control (AC) is seen after rehabilitation. The ProKAR study (Prospektive Katamnesestudie Asthma-Rehabilitation) was performed to provide data concerning the short- and long-term impact of PR on AC. Methods: Two-hundred one adult patients with mild to severe persistent asthma were prospectively followed one year after completion of a 3-week PR program. AC, the primary outcome parameter, and health-related quality of life (HRQoL) were monitored using the Asthma Control Test (ACT) and St. George's Respiratory Questionnaire (SGRQ) at initiation (T0) and end of the PR (T1) and 3, 6 and 12 months thereafter. Pulmonary function, physical fitness (6MWD) and asthmatic inflammation (FENO) were measured at T0 and T1. Results: The proportion of patients with well-controlled asthma (ACT score ≥20) increased from 33.2% to 67.3% after PR and was still at 51% after 12 months. Slight but statistically significant improvements in pulmonary functions and an increase in 6MWD of nearly 60 m were reported at T1. One year after discharge 55.8% of the patients still showed a clinically relevant improvement of at least 4 points in the total SGRQ score. Conclusions: The multidisciplinary inpatient PR program resulted in significant short and long-term improvement in AC and HRQoL in adult asthmatic patients.